In utero exposure to germinated brown rice and its oryzanol-rich extract attenuated high fat diet-induced insulin resistance in F1 generation of rats - Adamu, Hadiza Altine; Imam, Mustapha Umar; Ooi, Der Jiun; Mohd Esa, Norhaizan; Rosli, Rozita; Ismail, Maznah (BioMed Central, 2017)
Background: The development of insulin resistance is multifactorial, with maternal pre- and postnatal nutrition having significant influences. In this regard, high fat diet (HFD) feeding in pregnancy has been shown to increase risks of metabolic diseases. Thus, we investigated the effects of supplementation of HFD with germinated brown rice (GBR) and GBR-derived gamma oryzanol-rich extract (OE) on insulin resistance and its epigenetic implications in pregnant rats and their offsprings. Methods: Pregnant female Sprague dawley rats were fed with HFD alone, HFD + GBR or HFD + OE (100 or 200 mg/kg/day) throughout pregnancy and lactation. Their offsprings were weaned at 4 weeks post-delivery and were followed up until 8 weeks. Serum levels of adipokines were measured in dams and their offsprings, and global DNA methylation and histone acetylation patterns were estimated from the liver. Results: The dams and offsprings of the GBR and OE groups had lower weight gain, glycemic response, 8-Iso prostaglandin, retinol binding protein 4 and fasting insulin, and elevated adiponectin levels compared with the HFD group. Fasting leptin levels were lower only in the GBR groups. Hepatic global DNA methylation was lower in the GBR groups while hepatic H4 acetylation was lower in both GBR and OE dams. In the offsprings, DNA methylation and H4 acetylation were only lower in the OE group. However, dams and offsprings of the GBR and OE groups had higher hepatic H3 acetylation. Conclusions: GBR and OE can be used as functional ingredients for the amelioration of HFD-induced epigeneticallymediated insulin resistance.